2016
DOI: 10.1371/journal.pone.0148915
|View full text |Cite
|
Sign up to set email alerts
|

The Factors Related to CD4+ T-Cell Recovery and Viral Suppression in Patients Who Have Low CD4+ T Cell Counts at the Initiation of HAART: A Retrospective Study of the National HIV Treatment Sub-Database of Zhejiang Province, China, 2014

Abstract: BackgroundSince China has a unique system of delivering HIV care that includes all patients’ records. The factors related to CD4+ T-cell recovery and viral suppression in patients who have low CD4+ T cell counts at the initiation of HAART are understudied in the China despite subsequent virological suppression (viral load < 50 copies/mL) is unknown.MethodsThe authors conducted a retrospective cohort study using data from the national HIV treatment sub-database of Zhejiang province to identify records of HIV+ p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 38 publications
5
15
0
Order By: Relevance
“…Our study also demonstrated that patients ≥50 years demonstrated poorer immununologic recovery on ART, as shown by poorer CD4+ cell count recovery, compared to younger patients. The slow CD4+ cell count recovery in our older cohort is consistent with other studies which indicate that older individuals have a lower rate of increase in CD4+ cell counts following ART exposure compared to younger individuals [ 22 ]. This ability to increase CD4 cell count determined the risk of death in the multivariable model [ 23 , 24 ].…”
Section: Discussionsupporting
confidence: 91%
“…Our study also demonstrated that patients ≥50 years demonstrated poorer immununologic recovery on ART, as shown by poorer CD4+ cell count recovery, compared to younger patients. The slow CD4+ cell count recovery in our older cohort is consistent with other studies which indicate that older individuals have a lower rate of increase in CD4+ cell counts following ART exposure compared to younger individuals [ 22 ]. This ability to increase CD4 cell count determined the risk of death in the multivariable model [ 23 , 24 ].…”
Section: Discussionsupporting
confidence: 91%
“…Unlike other studies on IR [ 16 20 ], the present cohort study is limited to patients with sustained virological control to evaluate the immune systems’ maximum capacity to restore. So, patients were included if they: i) had a baseline count of aCD4, CD4% and CD4/CD8 collected ≤14 days prior to start ART; ii) received continuous ART for at least 1 year, iii) achieved an HIV-RNA <50 copies/ml during the first 24 weeks, and iv) maintained an undetectable viral load in ≥95% of the determinations throughout all the follow-up in order not to exclude subjects with occasional blips, defined as a positive viral load preceded and followed up by an undetectable viral load.…”
Section: Methodsmentioning
confidence: 99%
“…The following data were collected: date of HIV diagnosis, education and other social demographic characteristics, CD4 counts, transmission route, and routine follow-up and treatment information. The above databases have been described in detail in previous publications [ 24 , 25 ]. Prospective data were collected on patients who required VL testing in this study.…”
Section: Methodsmentioning
confidence: 99%